The Lachos women : Genealogy and cartography of power (Cajamarca, 17th century) - Argouse, Aude (2012)
This article discusses a phenomenon occurring in the regional archives of Cajamarca: the frequent use of the name Lachos, almost exclusively attributed to women. An examination of numerous 17th century notarial records, along with a census of September 1686, suggests that the surname Lachos was used to establish noble and founding lineages. Indeed, it is possible to reconstruct the dynasties of the caciques through the use of the female surname Lachos and its relation to the local lords. We also note the incursion of foreign women adopting the name, suggesting that is was a common practice to employ the name Lachos when settling in the locale.